Incidence Of Nuchal Cord Around The Neck And Its Impact On The Mode Of Delivery As Well As Fetal Outcomes (Journal of Pharmaceutical Negative Results, 2023)
Background: The nuchal membrane is a derivative of the yolk sac. It is a tube-like structure, 50 cm in length and sometimes circles the neck of the baby termed the nuchal cord.Objective: The present study aims to observe the incidence of the nuchal cord and its effect on the mode of delivery (MOD) along with fetal outcomesStudy design: A retrospective studyPlace and Duration: This study was conducted at Sobhraj Maternity Hospital Karachi from December 2021 to December 2022.Methodology: A total of 442 patients were initially considered in the present study, however, only 254 were enrolled after exclusion and inclusion criteria. The enrolled patients were divided into two groups. One group was the study group that contained 66 patients with the nuchal cord around the neck of the baby. The other group was the control group and which contained 188 patients with the normal position of the nuchal cord. The outcomes studies in the patients of both the groups were MOD, Apgar score >7 in the first and fifth minute, length of the nuchal cord, number of LSCS, staining of liquor with meconium, fetal distress, and admission in NICUResults: A total of 25.98% of patients had nuchal cord around the neck at delivery. The prevalence of nuchal cord was seen more in the primigravida pregnant patients and it was also statistically significant. The intrapartum, as well as postpartum risk, were not associated with the nuchal cord circling the neck. The mean length of the nuchal cord in the affected patients was greater than the normal patients in the control group with a significant p-value.Conclusion: The nuchal cord cannot be the only indication of caesarian section delivery. Overall3 loops of the nuchal cord increase the prevalence of delivery through operation and low Apgar score. Proper plotting of partogram and intrapartum surveillance result in optimal fetal outcomes.